Financial product conversion rate improving method based on federal learning and block chain - CAI QI (2023)
The invention provides a financial product conversion rate improving method based on federated learning and a block chain, and relates to the technical field of financial products. Comprising the following steps: S1, sending a model training request; s2, broadcasting a model training request; s3, responding to the model training request; s4, federal model training; S5, model evaluation; S6, reward allocation; and S7, potential customer mining. And S8, recommending financial products. According to the method, the product conversion rate model effect is improved, so that potential customer groups can be accurately identified, model training data are reserved in enterprises, the personal privacy of users is effectively protected, an effective benefit distribution mechanism is established, and the enthusiasm of enterprise subjects to participate in federal learning is improved; and meanwhile, the income obtained by each enterprise main body is recorded by utilizing the block chain, so that the integrity, the secu